CAPITAL STRUCTURE AND FINANCIAL LEVERAGE OF SUGARCANE AGRIBUSINESS COMPANIES: A MULTICASE STUDY FOR MIDDLE WEST (Gestão & Regionalidade, 2015)
This paper analyzed company groups from sugarcane agribusiness in the Brazilian Middle West to characterize their capital structures and financial leverage by calculating indebtedness, financial dependence and degree of financial leverage (DFL). The results demonstrate that agribusinesses in the Middle West are best suited to the pecking order theory because they adjust their debts according to their needs, and do not fit trade-off because of the difficulty of keeping the indebtedness within the average of this sector. In addition, there was a high level of debt inherent to the need for technological incorporations, increase in the production capacity and improvement of management features. Even with a high rate, the calculation of DFL showed that most business groups may also raise more funds from third parties, because the feedback given by the company is higher than the cost of debt. However, what limits the uptake of more third-party resources is the risks related to the activity, mainly crop failures, government control over fuel prices (gasoline) and tariff barriers.